1997
DOI: 10.1002/vnl.10179
|View full text |Cite
|
Sign up to set email alerts
|

A review of vinyl technology

Abstract: This is a review of PVC technology from chlorine and ethyle, to PVC polymerization, to melt processing, to properties, to recycling and environmental concerns. It is written in terms for understanding by even non‐scientists in the industry. PVC has a large sales volume, second only to polyethylene. Its high chlorine content provides it with a very high level of combustion resistance for building products, electrical enclosures, and wire & cable insulation. PVC has a unique ability to be compounded with a wide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 35 publications
1
22
0
1
Order By: Relevance
“…This is difference due to the insolubility of the PVC in its own monomer. The grain structures, containing agglomerates (coalesced primary particles ) are excellent evidence of typical PVC suspension grains. However, there is a major difference from common PVC suspension grains.…”
Section: Resultsmentioning
confidence: 92%
“…This is difference due to the insolubility of the PVC in its own monomer. The grain structures, containing agglomerates (coalesced primary particles ) are excellent evidence of typical PVC suspension grains. However, there is a major difference from common PVC suspension grains.…”
Section: Resultsmentioning
confidence: 92%
“…Figure 2.2 shows the effect of agitator speed on agglomeration. 101 Summers 102 shows an interesting photograph ( Figure 3.14) from early stages of polymerization. 101 Photograph A (0.1% conversion) shows that stable and uniform primary particles are formed.…”
Section: Suspension Polymerizationmentioning
confidence: 99%
“…Figure 3.13 shows morphology of early stages of polymerization. 102 Figure 3.15 shows morphology of suspension PVC at its final stage. Particles are stabilized by electrostatic forces.…”
Section: Suspension Polymerizationmentioning
confidence: 99%
“…This has motivated important lines of work in the development and applications of polymeric materials which are environmentally friendly, low toxicity and easily recyclable [2]. Within this research field, a marked interest has been showed in the improving of the formulations of one of the most widely consumed thermoplastics worldwide as the polyvinyl chloride (PVC), more specifically, the flexible polyvinyl chloride [3,4]. The use of this thermoplastic is especially sensitive to environmental impact and toxicity problems, since it is widely used in sectors such as plastic toys, childcare, food, packaging, medicalpharmacological...…”
Section: -Introductionmentioning
confidence: 99%